Adolescents in a wide-circulation territory of psychoactive substances: use and losses - Silva, Silas Zil da (2021)
It aimed to describe the profile of problems associated with substance use among adolescents, elementary school students from a school located in a territory with a high circulation of drugs, and to verify the relationships between use and sociodemographic characteristics. Cross-sectional and predictive correlational study, with 109 ninth-year students, who answered the questionnaire containing sociodemographic information and the Drug Use Screening Inventory (DUSI). The data were analyzed by descriptive statistics, association tests, and calculation of problem densities investigated by the DUSI. There was a greater density of problems for all areas of life investigated among students who had already used psychoactive substances. "Practice religion" was identified as a protective factor for the use of psychoactive substances and "work" as a risk factor for the use of alcohol. The need for preventive strategies directed to the use of substances and directed to this public was evidenced.